2015
DOI: 10.1177/0021886315569507
|View full text |Cite
|
Sign up to set email alerts
|

Does a Well-Informed Employee Have a More Positive Attitude Toward Change? The Mediating Role of Psychological Contract Fulfillment, Trust, and Perceived Need for Change

Abstract: This study examined the mediating role of psychological contract fulfillment, trust, and perceived need for change in the relationship between change information and employee attitude toward organizational change. As one of the first studies in organizational change research, attitude toward change was operationalized here as a tridimensional construct, comprising an affective, a behavioral, and a cognitive dimension. In a sample of 399 employees, data were gathered using questionnaires. The results confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 63 publications
1
29
1
3
Order By: Relevance
“…In so doing, the supervisors are shaping the subordinates’ perception of whether the psychological contract is being fulfilled and the subordinates should reciprocate accordingly. Furthermore, past research has shown that trust may influence one party's perception of whether the other party will fulfill the obligations of a psychological contract (Guest and Conway ; Van den Heuvell, Schalk and Marcel ). Thus, if the subordinates also trust the supervisors, these subordinates have greater confidence that their supervisors will fulfill their terms of the exchange relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In so doing, the supervisors are shaping the subordinates’ perception of whether the psychological contract is being fulfilled and the subordinates should reciprocate accordingly. Furthermore, past research has shown that trust may influence one party's perception of whether the other party will fulfill the obligations of a psychological contract (Guest and Conway ; Van den Heuvell, Schalk and Marcel ). Thus, if the subordinates also trust the supervisors, these subordinates have greater confidence that their supervisors will fulfill their terms of the exchange relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To do this, management should provide clear guidelines on how payouts will be determined, including how management will gather performance information, such as through supervisor evaluations, production numbers, and/or customer feedback. Indeed, the organizational change literature notes the importance of providing information in building support for change (Van den Heuvel, Schalk, & van Assen, 2015). Cichelli (2004) recommends that guidelines include the actual formulas for payout calculation, with easy-to-understand examples.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which e-internships may exhibit features commonly associated with psychological contracts (e.g., balanced, relational, transactional, or transitional contracts) may depend on the specific circumstances encountered in each e-internship. One characteristic may be key, namely, communication from both the employer and intern (see also Guest & Conway, 2002) as the effective use of communication supports clarification of organizational promises and commitments (Guest & Conway, 2002), particularly when employees face change or, we might argue, uncertainty as e-interns (van den Heuvel, Schalk & van Assen, 2015). Specifically, it is proposed that when technology is employed effectively to balance the needs of the business with the needs of the e-interns, psychological contracts in virtual internships may take more positive forms, reflecting mutually supportive relationships that provide room for skill and personal development.…”
Section: Psychological Contracts and E-internships: Research Questionsmentioning
confidence: 99%